Globalising Dublin: indicators of an urban society in transition - Niamh M. Moore (Dela, 2004)
Globalisation – political, economic or cultural - is controlled from, but is simultaneously shaping, urban places. Much of the recent research on globalisation and urban transformati-on has focused on the emergence of an international urban system. Within this system, the role and place of Dublin has been highly contested. This is due in part to the unique way in which the city has attempted to re-position itself within a global framework, but is also due to the difficulty in defining what actually constitutes a world city. Friedmann (1986) argues that one of the key characteristics of these places is that they become destination points for both domestic and international migrants, while Sassen (1991) argues that they are typified by significant socio-spatial polarisation. This paper examines some of the ways in which Dublin, a former peripheral city in global terms, is becoming increasingly embedded in the global urban system. It highlights how the city is beginning to exemplify many of the eco-nomic, social and cultural characteristics associated with ‘world cities’ and discusses a suitable framework for understanding this transition.